2014
DOI: 10.4183/aeb.2014.655
|View full text |Cite
|
Sign up to set email alerts
|

Male Reproductive Capacity, Evaluated by Testis Volume, Sperm Quality and Reproductive Hormones as an Ehnic Characteristic of the Population

Abstract: Lithuanian's male sperm quality was found to be much better as compared with other centres. The highest values of Kaunas young males were observed in total testicular volume, total sperm count, estradiol and SHBG. Parameters much higher than in other centres were sperm volume, normal morphology, sperm concentration, total motility, level of inhibin B and LH. These parameters are important for overall reproductive capacity of Lithuanians. Sperm quality and high spermatogenesis regulating hormone concentration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In 2003/2004 a comprehensive international study of male reproductive function which involved 18-25 year old young men from Denmark, Sweden, Finland, Norway, Estonia, Latvia and Lithuania was performed. Results of KELLY cohort from this study have previously been reported in publications concerning different aspects of their reproductive health (12,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In 2003/2004 a comprehensive international study of male reproductive function which involved 18-25 year old young men from Denmark, Sweden, Finland, Norway, Estonia, Latvia and Lithuania was performed. Results of KELLY cohort from this study have previously been reported in publications concerning different aspects of their reproductive health (12,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 75%
“…In the majority of our comparisons the baseline results of Lithuanian KELLY men are high normal (12). Some interesting results also come from Southern Spain (6).…”
Section: Questionsmentioning
confidence: 72%
See 2 more Smart Citations